Removal of sugar sweetened beverages from sale in a hospital setting—Consumer opinion and influence on purchasing behavior. (17th November 2021) - Tinney, Melissa; Rittinger, Rowena; Tomlinson, Kate; Borg, Dan; Warzel, Aleksandra; O'Sullivan, Mairead; Nyanhanda, Tafadzwa
Abstract: Issue addressed: This study investigated the impact of removing sugar sweetened beverages (SSBs) from sale in a regional health service. Drink purchasing patterns were measured by product ordering data. Consumer opinion regarding the intervention, self‐reported packaged drink purchase and consumption were also explored. Methods: Packaged drinks were classified into two categories, SSB or non‐SSB and drink types. Drink sales were determined by the collection of product ordering data for all packaged drink types sold, six months prior to and twelve months after the removal of SSBs. A consumer survey was undertaken six months after SSB removal to assess consumer opinion regarding SSB removal, self‐reported SSB consumption and purchase. Descriptive and Wilcoxon rank‐sum tests analyses assessed differences in packaged drinks purchase, self‐reported SSB consumption and purchase. Open‐ended survey responses were thematically analysed. Results: The median monthly number of juices, and diet drinks ordered increased significantly ( P = .05). 59% of the survey respondents regularly consumed SSBs and 58% agreed or strongly agreed with removing SSBs from sale. However, some consumers felt it was a removal of their freedom of choice. Conclusions: Removing SSBs from sale can result in consumers making healthier purchases. There was support for the initiative as it is seen as the responsibility of the health service to role model healthy eating behaviours. So what?: This study indicates removal of SSBs from sale is a promising health promotion intervention that can contribute to positive behaviour change, and potentially influence longer‐term health and wellbeing.